The Combination Of Money Laundering Crime With The Origin Of Narkotics Crime To Islamic Law - Ariman Sitompul; Mhd Nasir Sitompul (Proceeding International Seminar of Islamic Studies, 2019)
Money laundering is basically a further criminal act contained in one of the original criminal acts contained in Law No. 8 of 2010. In this case the origin of narcotics crime. The combination of these crimes involves assets, income, and assets disguised so that they can be used without being detected that the assets originated from illegal activities. Money laundering through income or assets originating from narcotics crime is an illegal activity that is converted into financial assets that appear to come from legitimate sources.The purpose of this study is to find out how the concept of Islamic economics combines the crime of money laundering with the origin of the narcotics crime, how to solve the problem.This study uses a qualitative approach using literature. Criminal research is very interesting because it combines two criminal acts of origin where these two criminal acts are not contained in the newspaper, interestingly investigated the combination of these crimes is an extraordinary crime both state and inter-state. These crimes are crimes that are very damaging to the state, society because it can damage the nation's future and damage the national economy, especially the stability of state finances.This completely contradicts Tasyri 'purpose of preventing harm and creating benefits. The view of Islamic law towards combining such acts is part of an immoral act that leaves the commandments of Allah and does something that is prohibited.